Effect of Balance Strategy Exercise Combined with an Occupational Therapy–Based Home Program on Functional Mobility in Community-Dwelling Older Adults - Aniek Puspitosari; Ninik Nurhidayah (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Declines in balance ability and mobility are major factors that increase the risk of falls and reduce independence among community-dwelling older adults. Exercise programs targeting balance strategy exercises can improve postural control, while occupational therapy–based home programs help translate these improvements into meaningful daily activities. Objectives: This study aimed to examine the effect of balance strategy exercises combined with an occupational therapy–based home program on functional mobility among community-dwelling older adults. Methods: This study employed a pre-experimental one-group pre-test and post-test design involving 48 older adults living in RW VIII, Kemiri Village, Kebakkramat, Karanganyar. Functional mobility was measured using the Four Square Step Test. The intervention consisted of three stages of balance strategy exercises, including ankle strategy exercises, hip strategy exercises, and stepping strategy exercises, combined with an occupational therapy–based home program delivered according to a structured intervention module. Data were analyzed using a paired t-test after the normality assumption was confirmed using the Shapiro–Wilk test. Results: The results of the paired t-test indicated a significant difference before and after the intervention (p < 0.05). An improvement in Four Square Step Test scores was observed following the balance strategy exercise and occupational therapy–based home program intervention, with a mean difference of 1.372. The combined intervention significantly improved functional mobility among older adults (p = 0.000). Most participants belonged to the elderly age group (76%), and 80% of the participants were female. Conclusion: The findings indicate that balance strategy exercises combined with an occupational therapy–based home program have a significant effect on improving functional mobility among community-dwelling older adults. Keywords: Balance Strategy Exercise, Occupational Therapy, Home Program, Functional Mobility, Community-Dwelling Older Adults.